The Impact of Banking Sector Performance on Economic Growth: A Case Study of Selected Countries of Central and Eastern Europe - Węgrzyn, Paweł; Kruszka, Michał (Comparative Economic Research. Central and Eastern Europe, 2025)
This study explores the complex relationship between banking sector performance and economic growth in Central and Eastern European (CEE) countries. Given the banking sector’s prominent role within the CEE financial system, our research examines its potential as a driver of economic growth using a fixed-effects panel regression model, focusing on four key variables: non-performing loans, total capital ratio, return on assets, and the ratio of bank assets to GDP. Granger causality tests further assess the directional nature of this relationship. Contrary to prevailing assumptions, the findings reveal no significant direct impact of banking sector performance on economic growth across the CEE region. Instead, the results of the Granger causality indicate that economic growth significantly bolsters the banking sector’s development, suggesting an inverse causality. These results offer valuable insights for policymakers, indicating that efforts to stimulate banking sector growth may benefit from prioritising economic development. The study contributes to a nuanced understanding of the CEE context, emphasizing the unique interplay between economic growth and banking sector development in post-transition economies.